Health education in shallot cultivation for the people of Pattalasang Village - Reviana Putri Andini; Evi Rusnadi; M. Yani Zamzam; Elva Angela (Universitas Muhammadiyah Magelang, 2023)
Pattallassang Village is one of the villages in the Pattallassang District, Gowa Regency, South Sulawesi Province, known for its abundant agricultural potential. Consequently, the majority of the population in this village earns a living as farmers. Shallots are one commodity with the potential to benefit its users in multiple ways. They serve as a valuable kitchen spice, known for their distinctive aroma and taste, and they also offer health benefits. This community service program aims to educate the public about the health benefits of shallots and the use of organic fertilizer in cultivation. The outcome of this initiative includes increased knowledge about the health benefits of shallots and improved skills in cultivating them using liquid organic fertilizer.